The Analysis of Seasonal Fluctuations and Correlation Between Monthly Average Exchange Rate of Main Currency and Monthly Average Import Prices of the Main Grain in Armenia - Aleksanyan, V. S.; Keshishyan, G. H.; Shirokov, S. N.; Trushkina, I. R. (ՀԱԱՀ հիմնադրամ)
Since 2020 the global economy has faced serious economic and financial challenges due to COVID-19 pandemic. The main purpose of this research is to study the dynamics of the monthly average import prices for the main types of imported grains and monthly average exchange rates for 1 US dollar in 2020-2022 in RA, disclosing the correlation between them. In the studied period the monthly average import price of wheat increased in autumn and in winter months. The results of analysis have shown that in the mentioned period there was a strong non-linear correlation between monthly average exchange rate of 1 US dollar and the average import prices of the main cereals.
Keywords: Agricultural Economics and Agribusiness